Predicting cetuximab accumulation in KRAS wild‐type and KRAS mutant colorectal cancer using (64)Cu‐labeled cetuximab positron emission tomography - Achmad, Arifudin (Cancer Sci, 2012)
Overexpression of epidermal growth factor receptor (EGFR) is common in colorectal cancer. However, cetuximab as an EGFR‐targeting drug is useful only for a subset of patients and currently no single predictor other than V‐Ki‐ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS) mutation status has been established. In the present study, we investigated cetuximab accumulation in colorectal tumors and major organs using (111)In‐DOTA‐cetuximab. We also evaluated the potential of positron emission tomography (PET) imaging of (64)Cu‐DOTA‐cetuximab. Colorectal tumor xenografts with a different EGFR expression level and KRAS mutation status were subjected to in vivo biodistribution study and PET imaging at 48 h post‐injection of radiolabeled cetuximab. The EGFR expression levels on colorectal tumors were determined by ex vivo immunoblotting and ELISA. We found that KRAS wild‐type tumors had significantly higher (111)In‐DOTA‐cetuximab accumulation than KRAS mutant tumors (P < 0.001). Based on KRAS mutation status, a strong correlation was found between (111)In‐DOTA‐cetuximab tumor uptake and EGFR expression level (KRAS wild type: r = 0.988; KRAS mutant: r = 0.829), and between (64)Cu‐DOTA‐cetuximab tumor uptake with EGFR expression level (KRAS wild type: r = 0.838; KRAS mutant: r = 0.927). Significant correlation was also found between tumor uptake of (111)In‐DOTA‐cetuximab and (64)Cu‐DOTA‐cetuximab (r = 0.920). PET imaging with (64)Cu‐DOTA‐cetuximab allowed clear visualization of tumors. Both radiolabeled cetuximab had effectively visualized cetuximab accumulation in colorectal tumors with a wide variety of EGFR expression levels and different KRAS mutation status as commonly encountered in the clinical setting. Our findings suggest that this radioimmunoimaging therefore can be clinically translated as an in vivo tool to predict cetuximab accumulation in colorectal cancer patients prior to cetuximab therapy. (Cancer Sci 2012; 103: 600–605)